Tindakan Hukum Administrasi (Negara) Perpajakan Yang Dapat Berakibat Pada Tindakan Pidana - Nursadi, Harsanto (Jurnal Hukum & Pembangunan, 2018)
The enormous authority possessed by the fiscus in various matters, particularly in establishing tax reduction or abolition, is prone to abuse. Administrative act in the form of tax decision shall end up as a criminal offense of it is an abuse of authority or unlawful. In fact, there are many fiscus who perform taxation administrative acts that stray beyond the authority for their own personal interests or that of taxpayers. Certainly, theycause state loss; therefore, they can qualify as a criminal offense. Thesebeg a question: which taxation administrative acts are lawful and which ones constitute criminal offense?